A comparative study of different sol-gel coatings for sealing the plasma electrolytic oxidation (PEO) layer on AA2024 alloy. (1st March 2023) - Akbarzadeh, Sajjad; Paint, Yoann; Olivier, Marie-Georges
Highlights: Sealing ability of different sol-gel coatings for the PEO layer on AA2024. Electrochemical evaluation of the duplex coatings via SVET and EIS techniques. The crucial role of compactness, hydrophobicity, and impregnation for the sol-gel sealing. PSG-ZT illustrated the best sol-gel sealing for the PEO layer. Insufficient sealing and hydrophilic properties of the PSG-AP for the PEO coating. Abstract: Owing to the inherent porosity of the coatings produced through the PEO process, the application of sol-gel coatings as a post-treatment has drawn immense attention thanks to their eco-friendly and reliable protective characteristics. Various parameters affect their performance, and the type of sol-gel precursors plays a significant role. In this study, various sol-gel precursors were used to prepare four types of PEO/sol-gel coating systems followed by an investigation of their sealing ability and corrosion resistance properties on AA2024 alloy. The corrosion prevention performance of the coatings was studied by electrochemical impedance spectroscopy (EIS) along with Scanning Vibrating Electrode Technique (SVET) analyzes. Some chemical characterization tests, such as Fourier Transform Infrared Spectroscopy (FT-IR) and rheology measurement, affirmed the influence of the sol-gel chemical composition on its compactness and the network viscosity. The distinctive sealing ability of different sol-gel coatings for the defects and pore filling of the PEO layer was visualized by Scanning Electron Microscope (SEM). To this end, different sol-gel formulations and various sol-gel network properties accordingly caused dissimilar sealing features for the PEO pores and, subsequently, the corrosion resistance of the duplex PEO/sol-gel coating is widely dependent on the used sol-gel precursors.